Contribuições sindicais: o direito fundamental da liberdade sindical e as modalidades de financiamento dos sindicatos - Oliveira Neto, Alberto Emiliano de (2008)
The objective is the analysis of trade union freedom from the parameters defined by International Declarations of Human Rights, seeking to attribute it the status of fundamental right. Duly bounded, trade union freedom will be faced with the kinds of contributions in the existing trade union law homeland. The result of the work is the proof that the whole mode of contribution imposed on workers and employers to certain non-affiliated trade union entails a violation of the fundamental right trade union freedom. As an alternative, it is the analysis of the contribution of solidarity, whose adoption, although marked by reservations, trade union freedom can reconcile the interests of trade unions